Pengembangan Media Video Pembelajaran Pada Materi Teknik Dasar Bola Basket Siswa SMK Negeri 1 Kota Lubuklinggau - Admanegara, Doni; Suhdy, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to develop learning video media on basic basketball technical material and to determine the quality of the video in terms of validity and practicality. This research is development research which refers to the development of a modified ADDIE model in 3 stages, namely Analysis, Design, and Development. The instruments used to measure the quality of the learning videos developed include validation sheets and practicality questionnaires. The product of this research is a video on basic basketball techniques at SMK Negeri 1 Lubuklinggau. The data analysis technique using linguist validity measures obtained a score of 82.9. material experts got a score of 87.5 and media experts got a score of 74. Based on the results of the validation assessment above, it can be seen that the learning media developed meets the Valid criteria in all aspects. In conclusion, that the learning media developed is valid and suitable to be tested on students. Keywords: Bola Basket, Video Media, Basic Techniques, Basketball, SMK Negeri 1 Lubuklinggau